Phosphorylation of CIITA directs its oligomerization, accumulation and increased activity on MHCII promoters - Tosi, Giovanna (Oxford University Press, 2002)
The class II transactivator (CIITA) is the master regulator of major histocompatibility complex class II (MHCII) transcription. Its activity is regulated at the post-transcriptional level by phosphorylation and oligomerization. This aggregation mapped to and depended on the phosphorylation of residues between positions 253 and 321 in CIITA, which resulted in a dramatic accumulation of the protein and increased expression of MHCII genes in human promonocytic U937 cells, which represent immature antigen-presenting cells. Thus, the post-transcriptional modification of CIITA plays an important role in the immune response.